Gut Bacterial Flora of Open Nested Honeybee, Apis florea - Ganeshprasad, D. N.; Lone, Jafar K.; Jani, Kunal; Shouche, Yogesh S.; Khan, Khalid Ali; Sayed, Samy; Shukry, Mustafa; Dar, Showket A.; Mushtaq, Muntazir; Sneharani, A. H. (Frontiers in Ecology and Evolution, 2022)
Honeybees are eusocial insects with close interaction with their surrounding environment. Gut microbiota in honeybees play a significant role in host health, biology, and interaction behavior with the surrounding environment. Apis florea, a wild bee, is the most primitive among all honeybees and is indigenous to the Indian subcontinent. Previous reports on reared honeybee species provide information on the gut microbiome. No such studies are reported on the gut microbiota of the wild honeybee species. This study aimed at studying the gut microbiome of the wild honeybee species, A. florea. The study reports the analysis and the identification of gut bacteria in the wild honeybee species, A. florea, employing culture-based and culture-independent methods. Cultured bacteria were identified and characterized by MALDI-TOF MS and 16S rRNA sequencing. A comprehensive analysis and identification of non-culturable bacteria were performed by 16S rRNA amplicon next-generation sequencing. This approach splits gut bacteria into four bacterial phyla, four families, and 10 genera in major. The dominant taxa identified in A. florea belonged to the family Enterobacteriaceae (79.47%), Lactobacillaceae (12.75%), Oxalobacteraceae (7.45%), and Nocardiaceae (0.13%). The prevailing bacteria belonged to Enterobacter, Lactobacillus, Escherichia-Shigella, Massilia, Klebsiella, Citrobacter, Pantoea, Serratia, Rhodococcus, and Morganella genera, belonging to phyla Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. This study observed the occurrence of a few bacteria that are not previously reported for their occurrence in other species of the Apis genus, making this investigation highly relevant with regard to the bee microbiome.